2015
DOI: 10.1038/jcbfm.2015.68
|View full text |Cite
|
Sign up to set email alerts
|

Blood and CSF biomarkers in brain subcortical ischemic vascular disease: Involved pathways and clinical applicability

Abstract: Vascular dementia is the second most common type of dementia after Alzheimer's disease (AD). Subcortical ischemic vascular disease refers to a form of vascular cognitive impairment characterized by the presence of diffuse white matter hyperintensities (WMHs) and multiple lacunar infarcts. These neuroimaging findings are mainly caused by cerebral smallvessel disease (cSVD) and relate to aging and cognitive impairment, but they can also be silent and highly prevalent in otherwise healthy individuals. We aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 135 publications
(134 reference statements)
0
37
0
Order By: Relevance
“…Elevated CSF/serum albumin ratios indicate BBB dysfunction and are correlated with WMI in subcortical ischemic vascular disease patients with dementia (Wallin et al, 2012). Other biomarkers such as plasma CRP, IL-6, homocysteine, urine albumin/creatinine ratio, and CSF MMP-9—all which are involved in inflammation and endothelial dysfunction—have been associated with WMI in patients with subcortical ischemic vascular disease (Vilar-Bergua et al, 2015). …”
Section: Imaging Analysis Of Wmimentioning
confidence: 99%
“…Elevated CSF/serum albumin ratios indicate BBB dysfunction and are correlated with WMI in subcortical ischemic vascular disease patients with dementia (Wallin et al, 2012). Other biomarkers such as plasma CRP, IL-6, homocysteine, urine albumin/creatinine ratio, and CSF MMP-9—all which are involved in inflammation and endothelial dysfunction—have been associated with WMI in patients with subcortical ischemic vascular disease (Vilar-Bergua et al, 2015). …”
Section: Imaging Analysis Of Wmimentioning
confidence: 99%
“…An increasing number of studies have investigated the role of blood biomarkers associated with age‐related WMHs in the past and a smaller number focused on SBIs, but very few of them have been replicated in other populations thus far . The most well‐known biomarkers are related to inflammation and endothelial dysfunction: C‐reactive protein, interleukin‐6, homocysteine, and urinary albumin‐to‐creatinine ratio or microalbuminuria …”
Section: Discussionmentioning
confidence: 99%
“…17 An increasing number of studies have investigated the role of blood biomarkers associated with age-related WMHs in the past and a smaller number focused on SBIs, but very few of them have been replicated in other populations thus far. 18 The most well-known biomarkers are related to inflammation and endothelial dysfunction: C-reactive protein, 19 interleukin-6, 20 homocysteine, 21 and urinary albumin-to-creatinine ratio or microalbuminuria. 22 Despite the heterogeneous set of proteins and lipids to which N-glycans structures can be attached, previous reports have described specific patterns in relation to several pathological conditions, such as NA2 for nonalcoholic steatohepatitis, 23 NA2FB for liver cirrhosis, 24 NA3Fb for hepatocellular carcinoma 25 or NG1A2F for type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Serum markers of hypercoagulability and markers of inflammation may lead to thrombosis, accelerated atherogenesis, and eventually resulting dementia of both Alzheimer's and vascular dementia(Gupta et al, 2005;Vilar-Bergua et al, 2016).Studies showed that high levels of the fibrinogen are related to brain atrophy, cognitive deficits, and Alzheimer's disease (AD)(Ahn et al, 2014;Gallacher et al, 2010;Tampubolon, 2016). Serum markers of hypercoagulability and markers of inflammation may lead to thrombosis, accelerated atherogenesis, and eventually resulting dementia of both Alzheimer's and vascular dementia(Gupta et al, 2005;Vilar-Bergua et al, 2016).Studies showed that high levels of the fibrinogen are related to brain atrophy, cognitive deficits, and Alzheimer's disease (AD)(Ahn et al, 2014;Gallacher et al, 2010;Tampubolon, 2016).…”
mentioning
confidence: 99%
“…esis of Alzheimer's disease. Serum markers of hypercoagulability and markers of inflammation may lead to thrombosis, accelerated atherogenesis, and eventually resulting dementia of both Alzheimer's and vascular dementia(Gupta et al, 2005;Vilar-Bergua et al, 2016).…”
mentioning
confidence: 99%